25.8: Difference between revisions

From testwiki
Jump to navigation Jump to search
 
 
Line 14: Line 14:
! scope="col" style="position: sticky; top: 0;" | Numeric<br>Mathematica
! scope="col" style="position: sticky; top: 0;" | Numeric<br>Mathematica
|-  
|-  
| [https://dlmf.nist.gov/25.8.E1 25.8.E1] || [[Item:Q7658|<math>\sum_{k=2}^{\infty}\left(\Riemannzeta@{k}-1\right) = 1</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\sum_{k=2}^{\infty}\left(\Riemannzeta@{k}-1\right) = 1</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>sum(Zeta(k)- 1, k = 2..infinity) = 1</syntaxhighlight> || <syntaxhighlight lang=mathematica>Sum[Zeta[k]- 1, {k, 2, Infinity}, GenerateConditions->None] == 1</syntaxhighlight> || Failure || Successful || Successful [Tested: 0] || Successful [Tested: 1]
| [https://dlmf.nist.gov/25.8.E1 25.8.E1] || <math qid="Q7658">\sum_{k=2}^{\infty}\left(\Riemannzeta@{k}-1\right) = 1</math><br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\sum_{k=2}^{\infty}\left(\Riemannzeta@{k}-1\right) = 1</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>sum(Zeta(k)- 1, k = 2..infinity) = 1</syntaxhighlight> || <syntaxhighlight lang=mathematica>Sum[Zeta[k]- 1, {k, 2, Infinity}, GenerateConditions->None] == 1</syntaxhighlight> || Failure || Successful || Successful [Tested: 0] || Successful [Tested: 1]
|-  
|-  
| [https://dlmf.nist.gov/25.8.E2 25.8.E2] || [[Item:Q7659|<math>\sum_{k=0}^{\infty}\frac{\EulerGamma@{s+k}}{(k+1)!}\left(\Riemannzeta@{s+k}-1\right) = \EulerGamma@{s-1}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\sum_{k=0}^{\infty}\frac{\EulerGamma@{s+k}}{(k+1)!}\left(\Riemannzeta@{s+k}-1\right) = \EulerGamma@{s-1}</syntaxhighlight> || <math>\realpart@@{(s+k)} > 0, \realpart@@{(s-1)} > 0</math> || <syntaxhighlight lang=mathematica>sum((GAMMA(s + k))/(factorial(k + 1))*(Zeta(s + k)- 1), k = 0..infinity) = GAMMA(s - 1)</syntaxhighlight> || <syntaxhighlight lang=mathematica>Sum[Divide[Gamma[s + k],(k + 1)!]*(Zeta[s + k]- 1), {k, 0, Infinity}, GenerateConditions->None] == Gamma[s - 1]</syntaxhighlight> || Failure || Aborted || Successful [Tested: 1] || Skipped - Because timed out
| [https://dlmf.nist.gov/25.8.E2 25.8.E2] || <math qid="Q7659">\sum_{k=0}^{\infty}\frac{\EulerGamma@{s+k}}{(k+1)!}\left(\Riemannzeta@{s+k}-1\right) = \EulerGamma@{s-1}</math><br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\sum_{k=0}^{\infty}\frac{\EulerGamma@{s+k}}{(k+1)!}\left(\Riemannzeta@{s+k}-1\right) = \EulerGamma@{s-1}</syntaxhighlight> || <math>\realpart@@{(s+k)} > 0, \realpart@@{(s-1)} > 0</math> || <syntaxhighlight lang=mathematica>sum((GAMMA(s + k))/(factorial(k + 1))*(Zeta(s + k)- 1), k = 0..infinity) = GAMMA(s - 1)</syntaxhighlight> || <syntaxhighlight lang=mathematica>Sum[Divide[Gamma[s + k],(k + 1)!]*(Zeta[s + k]- 1), {k, 0, Infinity}, GenerateConditions->None] == Gamma[s - 1]</syntaxhighlight> || Failure || Aborted || Successful [Tested: 1] || Skipped - Because timed out
|-  
|-  
| [https://dlmf.nist.gov/25.8.E3 25.8.E3] || [[Item:Q7660|<math>\sum_{k=0}^{\infty}\frac{\Pochhammersym{s}{k}\Riemannzeta@{s+k}}{k!2^{s+k}} = (1-2^{-s})\Riemannzeta@{s}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\sum_{k=0}^{\infty}\frac{\Pochhammersym{s}{k}\Riemannzeta@{s+k}}{k!2^{s+k}} = (1-2^{-s})\Riemannzeta@{s}</syntaxhighlight> || <math>s \neq 1</math> || <syntaxhighlight lang=mathematica>sum((pochhammer(s, k)*Zeta(s + k))/(factorial(k)*(2)^(s + k)), k = 0..infinity) = (1 - (2)^(- s))*Zeta(s)</syntaxhighlight> || <syntaxhighlight lang=mathematica>Sum[Divide[Pochhammer[s, k]*Zeta[s + k],(k)!*(2)^(s + k)], {k, 0, Infinity}, GenerateConditions->None] == (1 - (2)^(- s))*Zeta[s]</syntaxhighlight> || Failure || Successful || <div class="toccolours mw-collapsible mw-collapsed">Failed [1 / 6]<div class="mw-collapsible-content"><syntaxhighlight lang=mathematica>Result: -.1666666667
| [https://dlmf.nist.gov/25.8.E3 25.8.E3] || <math qid="Q7660">\sum_{k=0}^{\infty}\frac{\Pochhammersym{s}{k}\Riemannzeta@{s+k}}{k!2^{s+k}} = (1-2^{-s})\Riemannzeta@{s}</math><br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\sum_{k=0}^{\infty}\frac{\Pochhammersym{s}{k}\Riemannzeta@{s+k}}{k!2^{s+k}} = (1-2^{-s})\Riemannzeta@{s}</syntaxhighlight> || <math>s \neq 1</math> || <syntaxhighlight lang=mathematica>sum((pochhammer(s, k)*Zeta(s + k))/(factorial(k)*(2)^(s + k)), k = 0..infinity) = (1 - (2)^(- s))*Zeta(s)</syntaxhighlight> || <syntaxhighlight lang=mathematica>Sum[Divide[Pochhammer[s, k]*Zeta[s + k],(k)!*(2)^(s + k)], {k, 0, Infinity}, GenerateConditions->None] == (1 - (2)^(- s))*Zeta[s]</syntaxhighlight> || Failure || Successful || <div class="toccolours mw-collapsible mw-collapsed">Failed [1 / 6]<div class="mw-collapsible-content"><syntaxhighlight lang=mathematica>Result: -.1666666667
Test Values: {s = -2}</syntaxhighlight><br></div></div> || Successful [Tested: 6]
Test Values: {s = -2}</syntaxhighlight><br></div></div> || Successful [Tested: 6]
|-  
|-  
| [https://dlmf.nist.gov/25.8.E4 25.8.E4] || [[Item:Q7661|<math>\sum_{k=1}^{\infty}\frac{(-1)^{k}}{k}(\Riemannzeta@{nk}-1) = \ln@{\prod_{j=0}^{n-1}\EulerGamma@{2-e^{(2j+1)\pi i/n}}}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\sum_{k=1}^{\infty}\frac{(-1)^{k}}{k}(\Riemannzeta@{nk}-1) = \ln@{\prod_{j=0}^{n-1}\EulerGamma@{2-e^{(2j+1)\pi i/n}}}</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>sum(((- 1)^(k))/(k)*(Zeta(n*k)- 1), k = 1..infinity) = ln(product(GAMMA(2 - exp((2*j + 1)*Pi*I/n)), j = 0..n - 1))</syntaxhighlight> || <syntaxhighlight lang=mathematica>Sum[Divide[(- 1)^(k),k]*(Zeta[n*k]- 1), {k, 1, Infinity}, GenerateConditions->None] == Log[Product[Gamma[2 - Exp[(2*j + 1)*Pi*I/n]], {j, 0, n - 1}, GenerateConditions->None]]</syntaxhighlight> || Failure || Failure || Successful [Tested: 1] || <div class="toccolours mw-collapsible mw-collapsed">Failed [1 / 3]<div class="mw-collapsible-content"><syntaxhighlight lang=mathematica>Result: Plus[-0.6931471805599453, NSum[Times[Power[-1, k], Power[k, -1], Plus[-1, Zeta[k]]]
| [https://dlmf.nist.gov/25.8.E4 25.8.E4] || <math qid="Q7661">\sum_{k=1}^{\infty}\frac{(-1)^{k}}{k}(\Riemannzeta@{nk}-1) = \ln@{\prod_{j=0}^{n-1}\EulerGamma@{2-e^{(2j+1)\pi i/n}}}</math><br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\sum_{k=1}^{\infty}\frac{(-1)^{k}}{k}(\Riemannzeta@{nk}-1) = \ln@{\prod_{j=0}^{n-1}\EulerGamma@{2-e^{(2j+1)\pi i/n}}}</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>sum(((- 1)^(k))/(k)*(Zeta(n*k)- 1), k = 1..infinity) = ln(product(GAMMA(2 - exp((2*j + 1)*Pi*I/n)), j = 0..n - 1))</syntaxhighlight> || <syntaxhighlight lang=mathematica>Sum[Divide[(- 1)^(k),k]*(Zeta[n*k]- 1), {k, 1, Infinity}, GenerateConditions->None] == Log[Product[Gamma[2 - Exp[(2*j + 1)*Pi*I/n]], {j, 0, n - 1}, GenerateConditions->None]]</syntaxhighlight> || Failure || Failure || Successful [Tested: 1] || <div class="toccolours mw-collapsible mw-collapsed">Failed [1 / 3]<div class="mw-collapsible-content"><syntaxhighlight lang=mathematica>Result: Plus[-0.6931471805599453, NSum[Times[Power[-1, k], Power[k, -1], Plus[-1, Zeta[k]]]
Test Values: {k, 1, DirectedInfinity[1]}, Rule[GenerateConditions, None]]], {Rule[n, 1]}</syntaxhighlight><br></div></div>
Test Values: {k, 1, DirectedInfinity[1]}, Rule[GenerateConditions, None]]], {Rule[n, 1]}</syntaxhighlight><br></div></div>
|-  
|-  
| [https://dlmf.nist.gov/25.8.E5 25.8.E5] || [[Item:Q7662|<math>\sum_{k=2}^{\infty}\Riemannzeta@{k}z^{k} = -\EulerConstant z-z\digamma@{1-z}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\sum_{k=2}^{\infty}\Riemannzeta@{k}z^{k} = -\EulerConstant z-z\digamma@{1-z}</syntaxhighlight> || <math>|z| < 1</math> || <syntaxhighlight lang=mathematica>sum(Zeta(k)*(z)^(k), k = 2..infinity) = - gamma*z - z*Psi(1 - z)</syntaxhighlight> || <syntaxhighlight lang=mathematica>Sum[Zeta[k]*(z)^(k), {k, 2, Infinity}, GenerateConditions->None] == - EulerGamma*z - z*PolyGamma[1 - z]</syntaxhighlight> || Failure || Successful || Successful [Tested: 1] || Successful [Tested: 1]
| [https://dlmf.nist.gov/25.8.E5 25.8.E5] || <math qid="Q7662">\sum_{k=2}^{\infty}\Riemannzeta@{k}z^{k} = -\EulerConstant z-z\digamma@{1-z}</math><br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\sum_{k=2}^{\infty}\Riemannzeta@{k}z^{k} = -\EulerConstant z-z\digamma@{1-z}</syntaxhighlight> || <math>|z| < 1</math> || <syntaxhighlight lang=mathematica>sum(Zeta(k)*(z)^(k), k = 2..infinity) = - gamma*z - z*Psi(1 - z)</syntaxhighlight> || <syntaxhighlight lang=mathematica>Sum[Zeta[k]*(z)^(k), {k, 2, Infinity}, GenerateConditions->None] == - EulerGamma*z - z*PolyGamma[1 - z]</syntaxhighlight> || Failure || Successful || Successful [Tested: 1] || Successful [Tested: 1]
|-  
|-  
| [https://dlmf.nist.gov/25.8.E6 25.8.E6] || [[Item:Q7663|<math>\sum_{k=0}^{\infty}\Riemannzeta@{2k}z^{2k} = -\tfrac{1}{2}\pi z\cot@{\pi z}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\sum_{k=0}^{\infty}\Riemannzeta@{2k}z^{2k} = -\tfrac{1}{2}\pi z\cot@{\pi z}</syntaxhighlight> || <math>|z| < 1</math> || <syntaxhighlight lang=mathematica>sum(Zeta(2*k)*(z)^(2*k), k = 0..infinity) = -(1)/(2)*Pi*z*cot(Pi*z)</syntaxhighlight> || <syntaxhighlight lang=mathematica>Sum[Zeta[2*k]*(z)^(2*k), {k, 0, Infinity}, GenerateConditions->None] == -Divide[1,2]*Pi*z*Cot[Pi*z]</syntaxhighlight> || Failure || Failure || Error || <div class="toccolours mw-collapsible mw-collapsed">Failed [1 / 1]<div class="mw-collapsible-content"><syntaxhighlight lang=mathematica>Result: Plus[4.8091767343044744*^-17, NSum[Times[Power[0.5, Times[2, k]], Zeta[Times[2, k]]]
| [https://dlmf.nist.gov/25.8.E6 25.8.E6] || <math qid="Q7663">\sum_{k=0}^{\infty}\Riemannzeta@{2k}z^{2k} = -\tfrac{1}{2}\pi z\cot@{\pi z}</math><br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\sum_{k=0}^{\infty}\Riemannzeta@{2k}z^{2k} = -\tfrac{1}{2}\pi z\cot@{\pi z}</syntaxhighlight> || <math>|z| < 1</math> || <syntaxhighlight lang=mathematica>sum(Zeta(2*k)*(z)^(2*k), k = 0..infinity) = -(1)/(2)*Pi*z*cot(Pi*z)</syntaxhighlight> || <syntaxhighlight lang=mathematica>Sum[Zeta[2*k]*(z)^(2*k), {k, 0, Infinity}, GenerateConditions->None] == -Divide[1,2]*Pi*z*Cot[Pi*z]</syntaxhighlight> || Failure || Failure || Error || <div class="toccolours mw-collapsible mw-collapsed">Failed [1 / 1]<div class="mw-collapsible-content"><syntaxhighlight lang=mathematica>Result: Plus[4.8091767343044744*^-17, NSum[Times[Power[0.5, Times[2, k]], Zeta[Times[2, k]]]
Test Values: {k, 0, DirectedInfinity[1]}, Rule[GenerateConditions, None]]], {Rule[z, 0.5]}</syntaxhighlight><br></div></div>
Test Values: {k, 0, DirectedInfinity[1]}, Rule[GenerateConditions, None]]], {Rule[z, 0.5]}</syntaxhighlight><br></div></div>
|-  
|-  
| [https://dlmf.nist.gov/25.8.E7 25.8.E7] || [[Item:Q7664|<math>\sum_{k=2}^{\infty}\frac{\Riemannzeta@{k}}{k}z^{k} = -\EulerConstant z+\ln@@{\EulerGamma@{1-z}}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\sum_{k=2}^{\infty}\frac{\Riemannzeta@{k}}{k}z^{k} = -\EulerConstant z+\ln@@{\EulerGamma@{1-z}}</syntaxhighlight> || <math>|z| < 1, \realpart@@{(1-z)} > 0</math> || <syntaxhighlight lang=mathematica>sum((Zeta(k))/(k)*(z)^(k), k = 2..infinity) = - gamma*z + ln(GAMMA(1 - z))</syntaxhighlight> || <syntaxhighlight lang=mathematica>Sum[Divide[Zeta[k],k]*(z)^(k), {k, 2, Infinity}, GenerateConditions->None] == - EulerGamma*z + Log[Gamma[1 - z]]</syntaxhighlight> || Failure || Successful || Successful [Tested: 1] || Successful [Tested: 1]
| [https://dlmf.nist.gov/25.8.E7 25.8.E7] || <math qid="Q7664">\sum_{k=2}^{\infty}\frac{\Riemannzeta@{k}}{k}z^{k} = -\EulerConstant z+\ln@@{\EulerGamma@{1-z}}</math><br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\sum_{k=2}^{\infty}\frac{\Riemannzeta@{k}}{k}z^{k} = -\EulerConstant z+\ln@@{\EulerGamma@{1-z}}</syntaxhighlight> || <math>|z| < 1, \realpart@@{(1-z)} > 0</math> || <syntaxhighlight lang=mathematica>sum((Zeta(k))/(k)*(z)^(k), k = 2..infinity) = - gamma*z + ln(GAMMA(1 - z))</syntaxhighlight> || <syntaxhighlight lang=mathematica>Sum[Divide[Zeta[k],k]*(z)^(k), {k, 2, Infinity}, GenerateConditions->None] == - EulerGamma*z + Log[Gamma[1 - z]]</syntaxhighlight> || Failure || Successful || Successful [Tested: 1] || Successful [Tested: 1]
|-  
|-  
| [https://dlmf.nist.gov/25.8.E8 25.8.E8] || [[Item:Q7665|<math>\sum_{k=1}^{\infty}\frac{\Riemannzeta@{2k}}{k}z^{2k} = \ln@{\frac{\pi z}{\sin@{\pi z}}}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\sum_{k=1}^{\infty}\frac{\Riemannzeta@{2k}}{k}z^{2k} = \ln@{\frac{\pi z}{\sin@{\pi z}}}</syntaxhighlight> || <math>|z| < 1</math> || <syntaxhighlight lang=mathematica>sum((Zeta(2*k))/(k)*(z)^(2*k), k = 1..infinity) = ln((Pi*z)/(sin(Pi*z)))</syntaxhighlight> || <syntaxhighlight lang=mathematica>Sum[Divide[Zeta[2*k],k]*(z)^(2*k), {k, 1, Infinity}, GenerateConditions->None] == Log[Divide[Pi*z,Sin[Pi*z]]]</syntaxhighlight> || Failure || Successful || Successful [Tested: 1] || Successful [Tested: 1]
| [https://dlmf.nist.gov/25.8.E8 25.8.E8] || <math qid="Q7665">\sum_{k=1}^{\infty}\frac{\Riemannzeta@{2k}}{k}z^{2k} = \ln@{\frac{\pi z}{\sin@{\pi z}}}</math><br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\sum_{k=1}^{\infty}\frac{\Riemannzeta@{2k}}{k}z^{2k} = \ln@{\frac{\pi z}{\sin@{\pi z}}}</syntaxhighlight> || <math>|z| < 1</math> || <syntaxhighlight lang=mathematica>sum((Zeta(2*k))/(k)*(z)^(2*k), k = 1..infinity) = ln((Pi*z)/(sin(Pi*z)))</syntaxhighlight> || <syntaxhighlight lang=mathematica>Sum[Divide[Zeta[2*k],k]*(z)^(2*k), {k, 1, Infinity}, GenerateConditions->None] == Log[Divide[Pi*z,Sin[Pi*z]]]</syntaxhighlight> || Failure || Successful || Successful [Tested: 1] || Successful [Tested: 1]
|-  
|-  
| [https://dlmf.nist.gov/25.8.E9 25.8.E9] || [[Item:Q7666|<math>\sum_{k=1}^{\infty}\frac{\Riemannzeta@{2k}}{(2k+1)2^{2k}} = \frac{1}{2}-\frac{1}{2}\ln@@{2}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\sum_{k=1}^{\infty}\frac{\Riemannzeta@{2k}}{(2k+1)2^{2k}} = \frac{1}{2}-\frac{1}{2}\ln@@{2}</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>sum((Zeta(2*k))/((2*k + 1)*(2)^(2*k)), k = 1..infinity) = (1)/(2)-(1)/(2)*ln(2)</syntaxhighlight> || <syntaxhighlight lang=mathematica>Sum[Divide[Zeta[2*k],(2*k + 1)*(2)^(2*k)], {k, 1, Infinity}, GenerateConditions->None] == Divide[1,2]-Divide[1,2]*Log[2]</syntaxhighlight> || Failure || Successful || Successful [Tested: 0] || Successful [Tested: 1]
| [https://dlmf.nist.gov/25.8.E9 25.8.E9] || <math qid="Q7666">\sum_{k=1}^{\infty}\frac{\Riemannzeta@{2k}}{(2k+1)2^{2k}} = \frac{1}{2}-\frac{1}{2}\ln@@{2}</math><br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\sum_{k=1}^{\infty}\frac{\Riemannzeta@{2k}}{(2k+1)2^{2k}} = \frac{1}{2}-\frac{1}{2}\ln@@{2}</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>sum((Zeta(2*k))/((2*k + 1)*(2)^(2*k)), k = 1..infinity) = (1)/(2)-(1)/(2)*ln(2)</syntaxhighlight> || <syntaxhighlight lang=mathematica>Sum[Divide[Zeta[2*k],(2*k + 1)*(2)^(2*k)], {k, 1, Infinity}, GenerateConditions->None] == Divide[1,2]-Divide[1,2]*Log[2]</syntaxhighlight> || Failure || Successful || Successful [Tested: 0] || Successful [Tested: 1]
|-  
|-  
| [https://dlmf.nist.gov/25.8.E10 25.8.E10] || [[Item:Q7667|<math>\sum_{k=1}^{\infty}\frac{\Riemannzeta@{2k}}{(2k+1)(2k+2)2^{2k}} = \frac{1}{4}-\frac{7}{4\pi^{2}}\Riemannzeta@{3}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\sum_{k=1}^{\infty}\frac{\Riemannzeta@{2k}}{(2k+1)(2k+2)2^{2k}} = \frac{1}{4}-\frac{7}{4\pi^{2}}\Riemannzeta@{3}</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>sum((Zeta(2*k))/((2*k + 1)*(2*k + 2)*(2)^(2*k)), k = 1..infinity) = (1)/(4)-(7)/(4*(Pi)^(2))*Zeta(3)</syntaxhighlight> || <syntaxhighlight lang=mathematica>Sum[Divide[Zeta[2*k],(2*k + 1)*(2*k + 2)*(2)^(2*k)], {k, 1, Infinity}, GenerateConditions->None] == Divide[1,4]-Divide[7,4*(Pi)^(2)]*Zeta[3]</syntaxhighlight> || Failure || Successful || Successful [Tested: 0] || Successful [Tested: 1]
| [https://dlmf.nist.gov/25.8.E10 25.8.E10] || <math qid="Q7667">\sum_{k=1}^{\infty}\frac{\Riemannzeta@{2k}}{(2k+1)(2k+2)2^{2k}} = \frac{1}{4}-\frac{7}{4\pi^{2}}\Riemannzeta@{3}</math><br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\sum_{k=1}^{\infty}\frac{\Riemannzeta@{2k}}{(2k+1)(2k+2)2^{2k}} = \frac{1}{4}-\frac{7}{4\pi^{2}}\Riemannzeta@{3}</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>sum((Zeta(2*k))/((2*k + 1)*(2*k + 2)*(2)^(2*k)), k = 1..infinity) = (1)/(4)-(7)/(4*(Pi)^(2))*Zeta(3)</syntaxhighlight> || <syntaxhighlight lang=mathematica>Sum[Divide[Zeta[2*k],(2*k + 1)*(2*k + 2)*(2)^(2*k)], {k, 1, Infinity}, GenerateConditions->None] == Divide[1,4]-Divide[7,4*(Pi)^(2)]*Zeta[3]</syntaxhighlight> || Failure || Successful || Successful [Tested: 0] || Successful [Tested: 1]
|}
|}
</div>
</div>

Latest revision as of 12:04, 28 June 2021


DLMF Formula Constraints Maple Mathematica Symbolic
Maple
Symbolic
Mathematica
Numeric
Maple
Numeric
Mathematica
25.8.E1 k = 2 ( ζ ( k ) - 1 ) = 1 superscript subscript 𝑘 2 Riemann-zeta 𝑘 1 1 {\displaystyle{\displaystyle\sum_{k=2}^{\infty}\left(\zeta\left(k\right)-1% \right)=1}}
\sum_{k=2}^{\infty}\left(\Riemannzeta@{k}-1\right) = 1

sum(Zeta(k)- 1, k = 2..infinity) = 1
Sum[Zeta[k]- 1, {k, 2, Infinity}, GenerateConditions->None] == 1
Failure Successful Successful [Tested: 0] Successful [Tested: 1]
25.8.E2 k = 0 Γ ( s + k ) ( k + 1 ) ! ( ζ ( s + k ) - 1 ) = Γ ( s - 1 ) superscript subscript 𝑘 0 Euler-Gamma 𝑠 𝑘 𝑘 1 Riemann-zeta 𝑠 𝑘 1 Euler-Gamma 𝑠 1 {\displaystyle{\displaystyle\sum_{k=0}^{\infty}\frac{\Gamma\left(s+k\right)}{(% k+1)!}\left(\zeta\left(s+k\right)-1\right)=\Gamma\left(s-1\right)}}
\sum_{k=0}^{\infty}\frac{\EulerGamma@{s+k}}{(k+1)!}\left(\Riemannzeta@{s+k}-1\right) = \EulerGamma@{s-1}
( s + k ) > 0 , ( s - 1 ) > 0 formulae-sequence 𝑠 𝑘 0 𝑠 1 0 {\displaystyle{\displaystyle\Re(s+k)>0,\Re(s-1)>0}}
sum((GAMMA(s + k))/(factorial(k + 1))*(Zeta(s + k)- 1), k = 0..infinity) = GAMMA(s - 1)
Sum[Divide[Gamma[s + k],(k + 1)!]*(Zeta[s + k]- 1), {k, 0, Infinity}, GenerateConditions->None] == Gamma[s - 1]
Failure Aborted Successful [Tested: 1] Skipped - Because timed out
25.8.E3 k = 0 ( s ) k ζ ( s + k ) k ! 2 s + k = ( 1 - 2 - s ) ζ ( s ) superscript subscript 𝑘 0 Pochhammer 𝑠 𝑘 Riemann-zeta 𝑠 𝑘 𝑘 superscript 2 𝑠 𝑘 1 superscript 2 𝑠 Riemann-zeta 𝑠 {\displaystyle{\displaystyle\sum_{k=0}^{\infty}\frac{{\left(s\right)_{k}}\zeta% \left(s+k\right)}{k!2^{s+k}}=(1-2^{-s})\zeta\left(s\right)}}
\sum_{k=0}^{\infty}\frac{\Pochhammersym{s}{k}\Riemannzeta@{s+k}}{k!2^{s+k}} = (1-2^{-s})\Riemannzeta@{s}
s 1 𝑠 1 {\displaystyle{\displaystyle s\neq 1}}
sum((pochhammer(s, k)*Zeta(s + k))/(factorial(k)*(2)^(s + k)), k = 0..infinity) = (1 - (2)^(- s))*Zeta(s)
Sum[Divide[Pochhammer[s, k]*Zeta[s + k],(k)!*(2)^(s + k)], {k, 0, Infinity}, GenerateConditions->None] == (1 - (2)^(- s))*Zeta[s]
Failure Successful
Failed [1 / 6]
Result: -.1666666667
Test Values: {s = -2}

Successful [Tested: 6]
25.8.E4 k = 1 ( - 1 ) k k ( ζ ( n k ) - 1 ) = ln ( j = 0 n - 1 Γ ( 2 - e ( 2 j + 1 ) π i / n ) ) superscript subscript 𝑘 1 superscript 1 𝑘 𝑘 Riemann-zeta 𝑛 𝑘 1 superscript subscript product 𝑗 0 𝑛 1 Euler-Gamma 2 superscript 𝑒 2 𝑗 1 𝜋 𝑖 𝑛 {\displaystyle{\displaystyle\sum_{k=1}^{\infty}\frac{(-1)^{k}}{k}(\zeta\left(% nk\right)-1)=\ln\left(\prod_{j=0}^{n-1}\Gamma\left(2-e^{(2j+1)\pi i/n}\right)% \right)}}
\sum_{k=1}^{\infty}\frac{(-1)^{k}}{k}(\Riemannzeta@{nk}-1) = \ln@{\prod_{j=0}^{n-1}\EulerGamma@{2-e^{(2j+1)\pi i/n}}}

sum(((- 1)^(k))/(k)*(Zeta(n*k)- 1), k = 1..infinity) = ln(product(GAMMA(2 - exp((2*j + 1)*Pi*I/n)), j = 0..n - 1))
Sum[Divide[(- 1)^(k),k]*(Zeta[n*k]- 1), {k, 1, Infinity}, GenerateConditions->None] == Log[Product[Gamma[2 - Exp[(2*j + 1)*Pi*I/n]], {j, 0, n - 1}, GenerateConditions->None]]
Failure Failure Successful [Tested: 1]
Failed [1 / 3]
Result: Plus[-0.6931471805599453, NSum[Times[Power[-1, k], Power[k, -1], Plus[-1, Zeta[k]]]
Test Values: {k, 1, DirectedInfinity[1]}, Rule[GenerateConditions, None]]], {Rule[n, 1]}

25.8.E5 k = 2 ζ ( k ) z k = - γ z - z ψ ( 1 - z ) superscript subscript 𝑘 2 Riemann-zeta 𝑘 superscript 𝑧 𝑘 𝑧 𝑧 digamma 1 𝑧 {\displaystyle{\displaystyle\sum_{k=2}^{\infty}\zeta\left(k\right)z^{k}=-% \gamma z-z\psi\left(1-z\right)}}
\sum_{k=2}^{\infty}\Riemannzeta@{k}z^{k} = -\EulerConstant z-z\digamma@{1-z}
| z | < 1 𝑧 1 {\displaystyle{\displaystyle|z|<1}}
sum(Zeta(k)*(z)^(k), k = 2..infinity) = - gamma*z - z*Psi(1 - z)
Sum[Zeta[k]*(z)^(k), {k, 2, Infinity}, GenerateConditions->None] == - EulerGamma*z - z*PolyGamma[1 - z]
Failure Successful Successful [Tested: 1] Successful [Tested: 1]
25.8.E6 k = 0 ζ ( 2 k ) z 2 k = - 1 2 π z cot ( π z ) superscript subscript 𝑘 0 Riemann-zeta 2 𝑘 superscript 𝑧 2 𝑘 1 2 𝜋 𝑧 𝜋 𝑧 {\displaystyle{\displaystyle\sum_{k=0}^{\infty}\zeta\left(2k\right)z^{2k}=-% \tfrac{1}{2}\pi z\cot\left(\pi z\right)}}
\sum_{k=0}^{\infty}\Riemannzeta@{2k}z^{2k} = -\tfrac{1}{2}\pi z\cot@{\pi z}
| z | < 1 𝑧 1 {\displaystyle{\displaystyle|z|<1}}
sum(Zeta(2*k)*(z)^(2*k), k = 0..infinity) = -(1)/(2)*Pi*z*cot(Pi*z)
Sum[Zeta[2*k]*(z)^(2*k), {k, 0, Infinity}, GenerateConditions->None] == -Divide[1,2]*Pi*z*Cot[Pi*z]
Failure Failure Error
Failed [1 / 1]
Result: Plus[4.8091767343044744*^-17, NSum[Times[Power[0.5, Times[2, k]], Zeta[Times[2, k]]]
Test Values: {k, 0, DirectedInfinity[1]}, Rule[GenerateConditions, None]]], {Rule[z, 0.5]}

25.8.E7 k = 2 ζ ( k ) k z k = - γ z + ln Γ ( 1 - z ) superscript subscript 𝑘 2 Riemann-zeta 𝑘 𝑘 superscript 𝑧 𝑘 𝑧 Euler-Gamma 1 𝑧 {\displaystyle{\displaystyle\sum_{k=2}^{\infty}\frac{\zeta\left(k\right)}{k}z^% {k}=-\gamma z+\ln\Gamma\left(1-z\right)}}
\sum_{k=2}^{\infty}\frac{\Riemannzeta@{k}}{k}z^{k} = -\EulerConstant z+\ln@@{\EulerGamma@{1-z}}
| z | < 1 , ( 1 - z ) > 0 formulae-sequence 𝑧 1 1 𝑧 0 {\displaystyle{\displaystyle|z|<1,\Re(1-z)>0}}
sum((Zeta(k))/(k)*(z)^(k), k = 2..infinity) = - gamma*z + ln(GAMMA(1 - z))
Sum[Divide[Zeta[k],k]*(z)^(k), {k, 2, Infinity}, GenerateConditions->None] == - EulerGamma*z + Log[Gamma[1 - z]]
Failure Successful Successful [Tested: 1] Successful [Tested: 1]
25.8.E8 k = 1 ζ ( 2 k ) k z 2 k = ln ( π z sin ( π z ) ) superscript subscript 𝑘 1 Riemann-zeta 2 𝑘 𝑘 superscript 𝑧 2 𝑘 𝜋 𝑧 𝜋 𝑧 {\displaystyle{\displaystyle\sum_{k=1}^{\infty}\frac{\zeta\left(2k\right)}{k}z% ^{2k}=\ln\left(\frac{\pi z}{\sin\left(\pi z\right)}\right)}}
\sum_{k=1}^{\infty}\frac{\Riemannzeta@{2k}}{k}z^{2k} = \ln@{\frac{\pi z}{\sin@{\pi z}}}
| z | < 1 𝑧 1 {\displaystyle{\displaystyle|z|<1}}
sum((Zeta(2*k))/(k)*(z)^(2*k), k = 1..infinity) = ln((Pi*z)/(sin(Pi*z)))
Sum[Divide[Zeta[2*k],k]*(z)^(2*k), {k, 1, Infinity}, GenerateConditions->None] == Log[Divide[Pi*z,Sin[Pi*z]]]
Failure Successful Successful [Tested: 1] Successful [Tested: 1]
25.8.E9 k = 1 ζ ( 2 k ) ( 2 k + 1 ) 2 2 k = 1 2 - 1 2 ln 2 superscript subscript 𝑘 1 Riemann-zeta 2 𝑘 2 𝑘 1 superscript 2 2 𝑘 1 2 1 2 2 {\displaystyle{\displaystyle\sum_{k=1}^{\infty}\frac{\zeta\left(2k\right)}{(2k% +1)2^{2k}}=\frac{1}{2}-\frac{1}{2}\ln 2}}
\sum_{k=1}^{\infty}\frac{\Riemannzeta@{2k}}{(2k+1)2^{2k}} = \frac{1}{2}-\frac{1}{2}\ln@@{2}

sum((Zeta(2*k))/((2*k + 1)*(2)^(2*k)), k = 1..infinity) = (1)/(2)-(1)/(2)*ln(2)
Sum[Divide[Zeta[2*k],(2*k + 1)*(2)^(2*k)], {k, 1, Infinity}, GenerateConditions->None] == Divide[1,2]-Divide[1,2]*Log[2]
Failure Successful Successful [Tested: 0] Successful [Tested: 1]
25.8.E10 k = 1 ζ ( 2 k ) ( 2 k + 1 ) ( 2 k + 2 ) 2 2 k = 1 4 - 7 4 π 2 ζ ( 3 ) superscript subscript 𝑘 1 Riemann-zeta 2 𝑘 2 𝑘 1 2 𝑘 2 superscript 2 2 𝑘 1 4 7 4 superscript 𝜋 2 Riemann-zeta 3 {\displaystyle{\displaystyle\sum_{k=1}^{\infty}\frac{\zeta\left(2k\right)}{(2k% +1)(2k+2)2^{2k}}=\frac{1}{4}-\frac{7}{4\pi^{2}}\zeta\left(3\right)}}
\sum_{k=1}^{\infty}\frac{\Riemannzeta@{2k}}{(2k+1)(2k+2)2^{2k}} = \frac{1}{4}-\frac{7}{4\pi^{2}}\Riemannzeta@{3}

sum((Zeta(2*k))/((2*k + 1)*(2*k + 2)*(2)^(2*k)), k = 1..infinity) = (1)/(4)-(7)/(4*(Pi)^(2))*Zeta(3)
Sum[Divide[Zeta[2*k],(2*k + 1)*(2*k + 2)*(2)^(2*k)], {k, 1, Infinity}, GenerateConditions->None] == Divide[1,4]-Divide[7,4*(Pi)^(2)]*Zeta[3]
Failure Successful Successful [Tested: 0] Successful [Tested: 1]